Solubilization, Activation and Partial Purification of a Sialidase from Horse Liver - KRISHNA PURNAWAN CANDRA; PETER ROGGENTIN; ROLAND SCHAUER (Bogor Agricultural University, Indonesia, 2005)
Using sialyl-methylumbelliferyl -glycoside as substrate, sialidase in horse liver was detected as a membrane-bound enzyme. A yield of about 50% of sialidase activity was found in supernatant when solubilized in 0.1 M sodium-phosphate buffer pH 5.5, containing 0.15 M NaCl, 0.25 M sucrose, and 0.5% Triton X-100. Sialidase in the solubilisate could be activated by incubating in acidic pH at 37 oC. Incubation of this solubilized enzyme at 37 oC for 1.5 h at pH 5.0 led to 10% increase of activity and to the precipitation of about 50% of contaminating protein. Using cation-exchange chromatography on S-Sepharose FF and affinity chromatography on p-aminophenyl oxamic acid-agarose following solubilization and activation, about 6% of total sialidase activity was recovered with the purification factor of about 500. The pH and temperature optimum were measured at pH 4.3 and between 37-45 oC, respectively. Neu5Ac2en was a strong inhibitor, while p-aminophenyl oxamic acid had only a weak inhibitory effect.